The effect of premature polymerization from ambient light on the working time and fracture toughness of visible light curing composites - Chiu, Joanna JN; Pabustan, Christine AA.; Sunico, Michelle C.
This study aims to determine
Keywords: Premature polymerization; Working time; Composite; Ambient light; Fracture toughness